Peran Koperasi dalam Meningkatkan Kesejahteraan Ekonomi Santri dan Infrastruktur di Pondok Pesantren Miftahul Ulum RU IV Putra - Sehid Sehid; Roisul Adib (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In the economic sector, cooperatives are one form of collaboration in the field of economics. People trust this type of collaboration because they share a number of common needs in their lives. One of the pesantren-owned enterprises (BUMP) at Pondok Miftahul Ulum RU IV Putra is a cooperative that works to support and improve the local economy. This study aims to examine the role of Islamic boarding school cooperatives (kopontren) in improving students’ economic welfare and their contribution to the development of pesantren infrastructure. The research was conducted at Pondok Pesantren Miftahul Ulum RU IV Putra using a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that kopontren plays a strategic role in meeting students’ basic needs at affordable prices and serves as a practical learning platform that fosters entrepreneurship and self-reliance among students. Additionally, although its contribution to infrastructure is still limited, the kopontren has shown social concern through the provision of supporting facilities such as dormitory furniture and environmental maintenance. Collaboration between the cooperative management and pesantren leadership is a key factor in ensuring the sustainability of the cooperative as an integral part of the pesantren’s educational system.